1983
DOI: 10.1111/j.1365-246x.1983.tb02804.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity and rates of relative motion on the plate boundaries of Western North America

Abstract: The consistency of earthquake data and plate tectonic models and other estimates of fault slip, may be tested by estimating rates of motion from the earthquakes using the concept of seismic moment. The contribution of individual events may simply be summed, but a generally better estimate of long-term average slip rate is obtained by integration over magnitudefrequency of occurrence relations. Estimates of fault motion rates associated with earthquakes are possible within about a factor of 2 using this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 58 publications
1
83
1
Order By: Relevance
“…For example, Anderson [1979] found an overall agreement between observed catalog statistics and those derived from fault slip rates in southern California. Similarly, Hyndman and Weichert [1983] found that fault slip rates derived from earthquake catalogs and from plate tectonic models agreed well for offshore western Canada. However, both studies noted cases of significant disagreement between catalog statistics and geological estimates, which they attributed to aseismic deformation, elastic strain, or under-sampling of the earthquake catalog.…”
Section: Gps/seismicity Comparisons In Other Studiesmentioning
confidence: 69%
See 3 more Smart Citations
“…For example, Anderson [1979] found an overall agreement between observed catalog statistics and those derived from fault slip rates in southern California. Similarly, Hyndman and Weichert [1983] found that fault slip rates derived from earthquake catalogs and from plate tectonic models agreed well for offshore western Canada. However, both studies noted cases of significant disagreement between catalog statistics and geological estimates, which they attributed to aseismic deformation, elastic strain, or under-sampling of the earthquake catalog.…”
Section: Gps/seismicity Comparisons In Other Studiesmentioning
confidence: 69%
“…A factor 6-20 increase of the catalog moment rate (equation (2)) requires: a magnitude-moment parameter increase (d by about 0.8-1.3 or c by about 0.1-0.2) much larger than those permitted by earthquake data [Ristau et al, 2005]; a multiplication of the asymmetry factor 8 by 6-20, well beyond the range of magnitude uncertainties [e.g., Hyndman and Weichert, 1983]; or a maximum magnitude increase of about 1.1-1.8, leading to unrealistic M X = 8.1-9.3.…”
Section: Reconciling Gps and Catalog Moment Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…A simple example is an oceanic transform fault, bounded by midocean ridge segments. In that case, a scaling change is associated with the maximum magnitude, which is characteristic of the fault area (Hyndman and Weichert, 1983). Smaller scale fault discontinuities, as well as jogs and bends have been shown put strong constraints on rupture propagation and arrest (Nielsen and Knopoff, 1998).…”
Section: Introductionmentioning
confidence: 99%